Hybrid Beamforming Design for OFDM Dual-Function Radar-Communication System with Double-Phase-Shifter Structure - Wang, Bowen; Cheng, Ziyang; Wu, Linlong; He, Zishu (2022 30th European Signal Processing Conference (EUSIPCO), 2022)
In this paper, the problem of the hybrid beamforming (HBF) for a millimeter wave (mmWave) orthogonal frequency division multiplexing (OFDM) dual-function radar-communication (DFRC) system in the presence of signal-dependent interference is studied. The HBF network is based on the subarray connection architecture combining with the double-phase-shifter (DPS) structure. To achieve the dual functionality, we formulate the problem by maximizing the communication spectral efficiency subject to the constraints of radar integrated side-lobe to main-lobe ratio (ISMR), space-frequency nulling (SFN) and energy. An efficient algorithm based on the consensus alternating direction method of multipliers (CADMM) frame-work is developed to tackle the resultant nonconvex problem. Simulation results demonstrate the superiority of the proposed DPS structure and HBF algorithm.